Inside Risks Through Computer Architecture, Darkly: Total-system hardware and microarchitectural issues are becoming increasingly critical. - Markettos, A. T.; Watson, R. N. M.; Moore, S. W.; Sewell, P.; Neumann, P. G. (Communications of the ACM, 2019)
The article discusses risks and vulnerabilities associated with total-system hardware and computer microarchitecture. Topics include the time and cost hindrance associated with patches or software upgrades, the importance for designers to understand the layers of computer hardware and how it works as hardware definition languages are compiled to connections between library logic cells, and the use of CHERI system architecture to enable more secure implementation of insecure languages.